Effect on the Optical Efficiency and Photostability of Luminescent Solar Concentrator Based on the Deposition of Agsio2@Nps - (:unkn) unknown (American Chemical Society, 2020)
Because of the growing demand for the use of photovoltaic cells to transform solar energy into electrical energy, radiation concentration systems such as luminescent solar concentrators (LSCs) have gained significant attention. This work presents an LSC system based on the effect of SiO2-capped silver nanoparticles (AgSiO2@NPs) on the optical efficiency of the LSC. For this purpose, AgSiO2@NPs were deposited on a polymethylmethacrylate (PMMA) substrate using the layer-by-layer technique, and the luminescent material tetraphenylporphyrin (TPP) and Coumarin 6 were deposited by the spin-coating technique on a PMMA substrate with AgSiO2@NPs. Then, the emission analysis of the two systems (PMMA/AgSiO2@NPs/Coumarin 6 and PMMA/AgSiO2@NPs/TPP) demonstrates that the nanoparticles enhanced fluorescence 20 and 8 times for TPP and Coumarin 6, respectively. Finally, the optical efficiency of the LSC was determined using a photodiode system. The results show an increase in optical efficiency because of two effects, the amplification of the luminescence and the dispersion caused by the nanoparticles, obtaining a maximum efficiency of 1.8 for our LSC system.